1995
DOI: 10.1002/yea.320111509
|View full text |Cite
|
Sign up to set email alerts
|

Yeast sequencing reports. Molecular cloning and sequencing of the hcs gene, which encodes 3‐hydroxy‐3‐methylglutaryl coenzyme a synthase of Schizosaccharomyces pombe

Abstract: We have cloned and sequenced the hcs gene, which is thought to encode a 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) synthase consisting of 447 amino acids, from the fission yeast Schizosaccharomyces pombe. The predicted amino acid sequence of the hcs product of S. pombe has homology with the HMG-CoA synthase of rat (47.8%), chicken (49.2%), hamster (47.1%) and human cells (46.9%). One of the hcs genes was replaced with a marker gene in the diploid cell. No viable hcs-disrupted haploid was isolated after te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…1992); Bg , Blattella germanica (Martinez‐Gonzalez et al . 1993) and Sp , Schizosaccharomyces pombe (Katayama et al . 1995).…”
Section: Resultsmentioning
confidence: 99%
“…1992); Bg , Blattella germanica (Martinez‐Gonzalez et al . 1993) and Sp , Schizosaccharomyces pombe (Katayama et al . 1995).…”
Section: Resultsmentioning
confidence: 99%
“…hmgl + protein levels were elevated when HMG-CoA synthase was overproduced HMG-CoA synthase catalyses the synthesis of HMG-CoA from acetoacetyl-CoA (Goldstein and Brown, 1990), producing the substrate of HMG-CoA reductase. We expressed HMG-CoA synthase under the control of the constitutive adh+ promoter in the plasmid, pSOl (Katayama et al, 1996). We found that overexpression of HMG-CoA synthase resulted in an approximately 1.6-fold increase of native levels of hmgl+ protein ( Figure 11).…”
Section: The Hmgl + Protein Was An Integral Membrane Proteinmentioning
confidence: 98%
“…BjHMGS1 from B. juncea (Bj) [33]; HMGS from A. thaliana (At) [30]; P. sylvestris (Ps) [31]; Homo sapiens (Hs) [41]; Mus musculus (Mm) [42]; Gallus gallus (Gg) [43]; B. germanica (Bg) [44] and Schizosaccharomyces pombe (Sp) [45]. Amino acid residues selected for in vitro mutagenesis are in bold.…”
Section: Figure 4 Alignment Of Deduced Amino Acid Sequences For Hmgs mentioning
confidence: 99%